Flawless consulting : a guide to getting your expertise used - Block, Peter, 1939- (San Francisco : Pfeiffer, 2011)
"Flawless Consulting is considered the "consultant's bible" and a landmark bestseller that explains how to deal effectively with clients, peers, and others. This third edition addresses business and new challenges since the second edition was written and also explores what's on the minds of "next generation" consultants. The book includes more guidance on how to ask better questions, ideas for the virtual world, suggestions for dealing with difficult clients, the challenges of international consulting, additional case studies, commentary, expanded guidelines on implementation, and more on how to ask good questions."--
1. A consultant by any other name . . . -- 2. Techniques are not enough -- 3. Flawless consulting -- 4. Contracting overview -- 5. The contracting meeting -- 6. The agonies of contracting -- 7. The internal consultant -- 8. Understanding resistance -- 9. Dealing with resistance -- 10: From diagnosis to discovery -- 11. Whole-system discovery -- 12. Discovering gifts, capacities, and possibilities -- 13. Get the picture -- 14. Preparing for feedback -- 15. Managing the meeting for action -- 16. Implementation; 17: The elements of engagement -- 18: Teacher as consultant -- 19. The heart of the matter.
Includes bibliographical refereces and index.
Keywords: Business consultants